The Implementation Of Zakat Management In Strengthening The Economy of Mustahik at The Muhammadiyah Zakat, Infak, and Sedekah Institution (Lazismu) In Kota Parepare - Abdil Dzil Arsy; Mahsyar, Mahsyar; Bahri, Andi; Muhammadun, Muzdalifah; Aminah, St. (Economos : Jurnal Ekonomi dan Bisnis, 2024)
This research discusses the implementation of zakat management at LAZISMu Kota Parepare and its implications for strengthening the economy of mustahik (zakat recipients) in Kota Parepare. The research problems are as follows: 1. How is the implementation of the main principles of zakat management at LAZISMu Kota Parepare? 2. What is the impact of zakat/ZIS funds from LAZISMu Kota Parepare on strengthening the economy of mustahik in Kota Parepare? The methods used to collect data in this study include observation, interviews, and documentation. The results of this study indicate that out of the eight zakat management principles formulated by Islamic scholars, LAZISMu Kota Parepare has, in essence, implemented all of them, although not fully or perfectly. LAZISMu Kota Parepare was only able to apply a small portion due to managing zakat based on its capacity and needs. The zakat/ZIS funds distributed by LAZISMu Kota Parepare have had an impact or contribution towards strengthening the economy of mustahik in Kota Parepare. Although LAZISMu Kota Parepare has not fully implemented the zakat management principles as ideally formulated by Muslim scholars and cannot yet be classified as utilizing modern management (which is effective, efficient, and productive), it still plays a role in the economic empowerment of mustahik. This means that it provides motivation and optimism for mustahik to potentially live decently or survive through the zakat funds, which are likely to be received regularly, at least once a year.